2023
DOI: 10.5194/egusphere-2023-2362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weak relationship between remotely detected crevasses and inferred ice rheological parameters on Antarctic ice shelves

Cristina Gerli,
Sebastian Rosier,
Hilmar Gudmundsson
et al.

Abstract: Abstract. Over the past decade, a wealth of research has been devoted to the detection of crevasses in glaciers and ice sheets via remote sensing and machine learning techniques. It is often argued that remotely sensed damage maps can function as early-warning signals for shifts in ice shelf conditions from intact to damaged states and can serve as an important tool for ice sheet modellers to improve future sea-level rise predictions. Here, we provide evidence for Filchner-Ronne and Pine Island ice shelves tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Our ice-penetrating radar observations of near-surface crevasses inland and across the grounding zone suggest that near-surface crevasses do not significantly change character as they advect onto the ice shelf and that many of these features are still confined to the near surface (Supplementary figures S6, S7). The depth of these features may explain the weak relationship found by Gerli et al (2023) between ice-shelf crevasses identified by Izeboud and Lhermitte (2023) and inferences of ice-shelf fluidity derived from contemporaneous surface velocity and ice thickness observations. Our results in connection with the findings of Gerli et al (2023) suggest that surface crevasses expressed in satellite remote sensing datasets (e.g.…”
Section: Ice-shelf Weakeningmentioning
confidence: 94%
See 1 more Smart Citation
“…Our ice-penetrating radar observations of near-surface crevasses inland and across the grounding zone suggest that near-surface crevasses do not significantly change character as they advect onto the ice shelf and that many of these features are still confined to the near surface (Supplementary figures S6, S7). The depth of these features may explain the weak relationship found by Gerli et al (2023) between ice-shelf crevasses identified by Izeboud and Lhermitte (2023) and inferences of ice-shelf fluidity derived from contemporaneous surface velocity and ice thickness observations. Our results in connection with the findings of Gerli et al (2023) suggest that surface crevasses expressed in satellite remote sensing datasets (e.g.…”
Section: Ice-shelf Weakeningmentioning
confidence: 94%
“…The depth of these features may explain the weak relationship found by Gerli et al (2023) between ice-shelf crevasses identified by Izeboud and Lhermitte (2023) and inferences of ice-shelf fluidity derived from contemporaneous surface velocity and ice thickness observations. Our results in connection with the findings of Gerli et al (2023) suggest that surface crevasses expressed in satellite remote sensing datasets (e.g. Lai et al, 2020;Zhao et al, 2022;Surawy-Stepney et al, 2023a;Izeboud and Lhermitte, 2023) only weakly affect the bulk viscosity of ice shelves.…”
Section: Ice-shelf Weakeningmentioning
confidence: 94%